Neuroscience for Pre-Clinical Students - LeClair, Renée J. (Open textbook library., 2022)
Neuroscience for Pre-Clinical Students covers neuroenergetics, neurotransmitters, neuropeptides, and selected amino acid metabolism and degradation. This USMLE-aligned text is designed for a first-year undergraduate medical course and is meant to provide the essential biochemical information from these content areas in a concise format to enable students to engage in an active classroom. Hence, it does not cover neurophysiology and neuroanatomy; and clinical correlates and additional application of content are intended to be provided in the classroom experience. The text assumes that the students will have completed medical school prerequisites (including the MCAT) in which they will have been introduced to the most fundamental concepts of biology and chemistry that are essential to understand the content presented here. With its focus on high-yield concepts, this resource will assist the learner later in medical school and for exam preparation. The 49-page text was created specifically for use by pre-clinical students at Virginia Tech Carilion School of Medicine and was based on faculty experience and peer review to guide development and hone important topics. Instructors reviewing, adopting, or adapting parts or the whole of the text are requested to register their interest at: https://bit.ly/interest-preclinical. Instructors and subject matter experts interested in and sharing their original course materials relevant to pre-clinical education are requested to join the instructor portal at https://www.oercommons.org/groups/pre-clinical-resources/10133.